Strategi Pemberitaan Diskominfo Medan Terhadap Kepercayaan dan Literasi Informasi Masyarakat di Kota Medan - Siti Sarah; Muhammad Alfikri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study aims to analyze the news reporting strategy implemented by the Medan City Communication and Informatics Office (Diskominfo) as a form of public communication practice and its impact on public trust and information literacy among urban communities. The study employed a descriptive qualitative approach. Data were collected through in-depth interviews, participant observation, and documentation. Informants were selected using purposive sampling, consisting of internal staff of the Medan City Diskominfo and members of the public as information recipients. The findings reveal that Diskominfo’s reporting strategy primarily focuses on the utilization of digital media platforms, particularly Instagram and TikTok, with a two-way communication pattern established through active social media interaction. From the public perspective, government information is perceived as accessible and relatively credible, although audiences still tend to independently verify the information they receive. The study also found that this reporting strategy contributes to improving public information literacy, despite uneven public abilities in filtering and evaluating information. The novelty of this research lies in its emphasis on the relationship between government digital reporting strategies, public trust, and information literacy within the context of urban digital communication. This study contributes to the development of public communication studies by demonstrating that government reporting functions not only as an information delivery mechanism but also as a strategic instrument for strengthening public trust and digital information literacy simultaneously.